Commune agroecosystem analysis to support decision making for water allocation for fisheries and agriculture in the Tonle Sap wetland system - Senaratna Sellamuttu, Sonali; Mith, S.; Chu Thai, H.; Johnston, R.; Baran, Eric; Dubois, Mark; Soeun, M.; Craig, I.; Nam, S.; Smith, L. (CGIAR Challenge Program on Water and Food, 2010)
The Project on Commune Agroecosystem Analysis to Support Decision Making for Water Allocation for Fisheries and Agriculture in the Tonle Sap Wetland System was undertaken with the aim of improving fisheries considerations in the Commune Agroecosystem Analysis (CAEA) process undertaken in Cambodia, to facilitate better planning at the commune level. Under this project a number of changes were made to the CAEA tools and process and pilot tested in an adaptive, iterative manner in four communes – two that had conducted a CAEA previously and two that had not. Results and analyses indicated that the project had significantly strengthened the manner in which livelihoods, water resources and fisheries are now addressed by CAEA. The revised CAEA guidance manual has also shown potential for having wider uptake, and a number of tools have been used by several other projects within Cambodia.